A REVIEW OF CURRENT NURSING PRACTICE AND EVIDENCE-BASED GUIDELINES IN ENTERAL NUTRITION IN THE CRITICALLY ILL PATIENT - Al kalaldeh, Mahmoud; Watson, Roger; Hayter, Mark (European Scientific Journal, ESJ, 2012)
Objectives: to provide an overview of evidence-based guidelines regarding some clinical practices related to enteral nutrition along with nursing adherence to these guidelines in the critically ill. Background: evidence-based guidelines for enteral nutrition curtailing the incidence of complications through managing gastric residual volumes, minimizing feeding interruption/under-feeding, confirming tube placement and preventing feeding system contamination. Design: an integrative literature review was employed to include various quantitative methodologies; however, RCTs predominated. Methods: electronic searching of CINAHL, Medline and Cochrane Library databases between 1995- 2011. Of 599 retrieved studies, 87 were included in the review. Results: The studies showed an inadequacy in nursing adherence to enteral nutrition evidence-based. Gastric residual volume should be strictly controlled using prokinetic agents, appropriate head of bed elevation and proper endo-tracheal tube cuff pressure. Feeding interruption should be avoided whenever is possible and an intentional increase to feeding rates/volumes are recommended to avoid under-feeding. X-ray and pH methods of confirming tube placement are more reliable and superior to capnometry and auscultatory methods. Feeding system hanging time should not exceed four consecutive days to prevent infection by endogenous source in addition to delivering formulae at closer body core temperature. Conclusion: evidence-based protocols should be employed effectively and consistently to eradicate discrepancies in nursing practice. Relevance to clinical practice: this paper highlights nursing role in prohibiting the majority of enteral nutrition complications through adhering to evidence-based guidelines.